2016
DOI: 10.1007/s10068-016-0143-2
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effects of lactic acid-fermented garlic extract against acetaminophen-induced acute liver injury in rats

Abstract: The aim of the present study was to investigate the protective effect of fermented garlic extract by lactic acid bacteria (LAFGE) against acetaminophen (AAP)-induced acute liver injury in rats. Here we demonstrated that rats treated with LAFGE exhibit resistance to AAP-induced liver injury accompanied by lowered plasma alanine amino transferase levels and decreased proinflammatory responses. This function of LAFGE is linked to its capacity of suppressing AAP-induced apoptosis in the liver, partly via the inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Compared with unfermented garlic extract, the fermented garlic extract by Lactobacillus plantarum BL2 (LAFGE) was able to more effectively reduce liver lipid levels and ameliorate hepatic steatosis in mice [142]. Another study revealed that LAFGE inhibited liver cell apoptosis partly by suppressing MAPK phosphorylation and down-regulating p53, which protected the liver from acetaminophen-induced injury in rats [143]. Furthermore, LAFGE was considered as a potential treatment for mild hepatic dysfunction.…”
Section: Biological Functions Of Garlicmentioning
confidence: 99%
“…Compared with unfermented garlic extract, the fermented garlic extract by Lactobacillus plantarum BL2 (LAFGE) was able to more effectively reduce liver lipid levels and ameliorate hepatic steatosis in mice [142]. Another study revealed that LAFGE inhibited liver cell apoptosis partly by suppressing MAPK phosphorylation and down-regulating p53, which protected the liver from acetaminophen-induced injury in rats [143]. Furthermore, LAFGE was considered as a potential treatment for mild hepatic dysfunction.…”
Section: Biological Functions Of Garlicmentioning
confidence: 99%
“…Other study showed that the hepatic steatosis was blocked in rats treated with heat-extracted aged black garlic in a high fatinduced liver steatosis rat model (Shin et al, 2014). It was also reported that LAFGE attenuated acetaminophen-induced liver injury by preventing apoptosis, inhibiting lipid peroxidation and increasing antioxidant enzymes (Lee et al, 2016). In the present study, we evaluated whether the hepatoprotective effect of LAFGE can be The hepatoprotective function of LAFGE has been reported due to its antioxidative properties, mainly attributed to the presence of organosulfur compounds like S-allyl cysteine (SAC) and cycloalliin (Allison, Lowe, & Rahman, 2006).…”
Section: Discussionmentioning
confidence: 93%
“…Other study showed that the hepatic steatosis was blocked in rats treated with heat‐extracted aged black garlic in a high fat‐induced liver steatosis rat model (Shin et al, ). It was also reported that LAFGE attenuated acetaminophen‐induced liver injury by preventing apoptosis, inhibiting lipid peroxidation and increasing antioxidant enzymes (Lee et al, ). In the present study, we evaluated whether the hepatoprotective effect of LAFGE can be enhanced by adding l ‐arginine, l ‐ornithine, and the leaf extract of licorice and artichoke, using a rat model of GalN/LPS‐induced acute liver injury.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…45 Another study results indicated that garlic extract had gastroprotective effects by noteworthy healing the damage of gastric mucosa and reduction in the total microbiome. 46 Garlic extract by lactic acid bacteria ameliorates liver injury through preventing oxidative stress-mediated 47 and garlic extract has hepatoprotective effects and advocates that garlic supplementation might be a one of the good adjuvant therapy for the management of liver injury. 48 Naji and colleagues have reported that administration of clove garlic had a significant reductive effect on liver function enzymes including serum alkaline phosphatase, aspartate aminotransferase and alanine aminotransferase levels and it also had been reported to play role in the improvement of some histological parameters.…”
Section: Hepatoprotective Effectmentioning
confidence: 99%